The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1055/a-0633-9098
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Achilles and Patellar Tendinopathy in Adolescent Elite Athletes

Abstract: The study investigated the incidence of Achilles and patellar tendinopathy in adolescent elite athletes and non-athletic controls. Furthermore, predictive and associated factors for tendinopathy development were analyzed. The prospective study consisted of two measurement days (M1/M2) with an interval of 3.2±0.9 years. 157 athletes (12.1±0.7 years) and 25 controls (13.3±0.6 years) without Achilles/patellar tendinopathy were included at M1. Clinical and ultrasound examinations of both Achilles (AT) and patellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…In particular, the Achilles tendon (AT) is predisposed for tendon injuries due to a considerably lower safety factor (ratio between ultimate failure stress and functional stress) in comparison to other tendons (Ker et al, 1988; Magnusson et al, 2001) and the prevalence of AT tendinopathies seems to increase after maturity in adult athletes (Cassel et al, 2018; Janssen et al, 2018). A recent study demonstrated higher m. triceps surae (TS) muscle strength and AT stiffness for the take-off leg in comparison to the swing leg in male collegiate track and field jumpers with somewhat higher inter-limb dissimilarities in AT stiffness in relation to muscle strength (Bayliss et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the Achilles tendon (AT) is predisposed for tendon injuries due to a considerably lower safety factor (ratio between ultimate failure stress and functional stress) in comparison to other tendons (Ker et al, 1988; Magnusson et al, 2001) and the prevalence of AT tendinopathies seems to increase after maturity in adult athletes (Cassel et al, 2018; Janssen et al, 2018). A recent study demonstrated higher m. triceps surae (TS) muscle strength and AT stiffness for the take-off leg in comparison to the swing leg in male collegiate track and field jumpers with somewhat higher inter-limb dissimilarities in AT stiffness in relation to muscle strength (Bayliss et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that prevalence and incidence of back pain as well as of lower extremity tendinopathies are underreported in young adolescent elite athletes (Cassel et al, 2015, 2018; Simpson et al, 2016; Müller et al, 2017). Due to the long-standing and the potentially chronifying character of the diseases early diagnostics and clear treatment strategies are mandatory, especially in adolescent elite athletes (Cook et al, 2016; Simpson et al, 2016; Hartvigsen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Bones are less mineralized and have reduced fracture toughness in young individuals resulting in a higher proportion of fractures concerning all sustained injuries during adolescence (Kontulainen et al, 2007; Darrow et al, 2009). Furthermore, it has been frequently reported that young adolescent athletes have an increased risk of sustaining severe and overuse skeletal injuries compared to non-athletes (Villemure and Stokes, 2009; Stracciolini et al, 2013; Cassel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a higher prevalence of structural intratendinous changes have been observed in adolescent athletes with patellar tendinopathy symptoms than those without [336]. In addition, intratendinous alterations that were associated with tendinopathies have been reported in adolescent youth athletes compared to recreationally active controls [337]. However, such issues may not only be impacted by training activity but also impacted by growth and maturation processes due to increases in aspects such as moment arm lengths and muscle activation, which leads to a disproportionate increase of muscle strength [338].…”
Section: Other Programming Considerationsmentioning
confidence: 99%